In vitro and in vivo evaluation of nanoliposomes loading quercetin and 3-bromopyruvate against glioma - Marvin Antonio Soriano-Ursúa; Angélica Vega-García; Vinnitsa Buzoianu-Anguiano; Ana Lilia Ocampo-Nestor; Joaquín Manjarrez-Marmolejo; Iris Angélica Feria-Romero (SpringerOpen, 2024)
Abstract Background Diffuse astrocytoma (a type of glioma) and its prevalence are matters of concern worldwide. Patients with this type of tumour have a poor prognosis because after surgical treatment, radiotherapy and/or chemotherapy, these tumours eventually regrow or progress. To date, there is no effective treatment that can cure affected patients. Quercetin and 3-bromopyruvate are chemical compounds that have been proven to have antitumour effects alone or in combination with other compounds. Nevertheless, combination treatments including these agents are not used for treating diffuse astrocytoma. Methods The use of nanoliposomes loaded with quercetin and 3-bromopyruvate as combination therapy was evaluated by treating C6 cells in vitro and in vivo (in Sprague-Dawley rat brain). Results The 0.5 mg/mL quercetin + 0.75 mg/mL 3-bromopyruvate combination treatment decreased the expression of the biomarkers Annexin V and Caspase-3 and inhibited tumour growth; this was consistent with the in vivo results that revealed the administration of this treatment resulted in improved animal survival. Conclusions The observations in the present study support the further exploration of this combination of active agents in the treatment of high-grade diffuse astrocytoma, especially in cases for which wide resection is possible.